SH.SEYTOVTÍŃ «XALQABAD» ROMANÍNDA SINONIM HÁM ANTONIMLERDIŃ STILLIK ÓZGESHELIKLERI - Abdiev, A.; Tolıbaev, A. (SCIENCE and SOCIETY, 2022)
The article discusses the stylistic features of the novel-tetrology by Sh. Seitov "Halkabad". A detailed analysis of synonyms and antonyms used in this work is also given.
Keywords: the language of fiction; the structure of dictionary; synonym; antonym; phraseological synonym